Ethnographies of educational and cultural conflicts strategies and resolutions - Jeffrey, Bob, 1946-; Walford, Geoffrey (Studies in educational ethnography, 2004)
National Curricula need to be interpreted in terms of the cultures and experience of learners and adjusted accordingly, for example a literacy and history curriculum needs to include perspectives relevant to the local culture. Teachers, learners, families and communities mediate, appropriate, subvert, and challenge the processes of policy implementation, curriculum engagement and pedagogic practices to make educational experiences more meaningful. These articles exemplify the conflicts, the coping strategies and resolutions adopted by those at the policy implementation interface. Examination of these processes using ethnographic methods identifies and characterises these tensions and provides research findings that can be used to construct lasting solutions that are commensurate with complex situations. The writers in this volume have carried out ethnographies that illuminate educational disjunctions, ambiguities and tensions, agency, strategic action and resolution. Their methodology enables them to show, in detail, how incongruencies arise, how contexts affect interactions, what kind of agency operates, and the circumstances leading to resolutions. Six articles focus on educational inequality, three on identity development and we include three that discuss methodological issues of partisanship in researching equality issues.